PENGEMBANGAN SOSIAL- EMOSIONAL ANAK MELALUI METODE ROLE PLAYING (BERMAIN PERAN) DI KELOMPOK B ANAK USIA DINI - Sri Jamilah (Pelangi Jurnal Pemikiran dan Penelitian Islam Anak Usia Dini, 2019)
This article is titled Child social-emotional development through the Role Playing method in Group B Early Childhood. The aim is to know the child’s social-emotional development through the Role Playing method in Group B of Early Childhood. Child social-emotional development through the Role Playing method (role playing) in Group B Early Childhood is the development of imagination and appreciation of children who act as subjects of active learning. Role playing activities discussed in this study are one of the efforts to improve children’s social emotional abilities by developing imagination and appreciation by students by acting as living figures or inanimate objects. This game is generally carried out by more than one person, it depends on what is played.